Analysis of the effects of microbiome-related confounding factors on the reproducibility of the volatolomic test. (24th June 2016) - Leja, Marcis; Amal, Haitham; Lasina, Ieva; Skapars, Roberts; Sivins, Armands; Ancans, Guntis; Tolmanis, Ivars; Vanags, Aigars; Kupcinskas, Juozas; Ramonaite, Rima; Khatib, Salam; Bdarneh, Shifaa; et al.
Abstract: Volatile organic compound (VOC) testing in breath has potential in gastric cancer (GC) detection. Our objective was to assess the reproducibility of VOCs in GC, and the effects of conditions modifying gut microbiome on the test results. Ten patients with GC were sampled for VOC over three consecutive days; 17 patients were sampled before and after H. pylori eradication therapy combined with a yeast probiotic; 61 patients were sampled before and after bowel cleansing (interventions affecting the microbiome). The samples were analyzed by: (1) gas chromatography linked to mass spectrometry (GC-MS), applying the non-parametric Wilcoxon test (level of significance p   <  0.05); (2) by cross-reactive nanoarrays combined with pattern recognition. Discriminant function analysis (DFA) was used to build the classification models; and leave-one-out cross-validation analysis was used to classify the findings. Exhaled VOCs profiles were stable for GC patients over a three day period. Alpha pinene ( p   =  0.028) and ethyl acetate ( p   =  0.030) increased after the antibiotic containing eradication regimen; acetone ( p   =  0.0001) increased following bowel cleansing prior to colonoscopy. We further hypothesize that S. boulardii given with the standard eradication regimen to re-establish the gut microbiome was the source for long-term ethyl acetate production. Differences between the initial and the follow-up sample were also revealed in the DFA analysis of the sensor data. VOC measurement results are well-reproducible in GC patients indicating a useful basis for potential disease diagnostics. However, interventions with a potential effect on the gut microbiome may have an effect upon the VOC results, and therefore should be considered for diagnostic accuracy.